До обґрунтування нормативної документації щодо забезпечення якості технічного сервісу сільськогосподарської техніки - Рубльов, В. І.; Войтюк, В. Д.; Рубльов, В. Є.; Rublov, Vladislav; Voytyuk, Valery; Rublov, Viktor (КНТУ, 2013)
Технічний сервіс є обов’язковою послугою, яка супроводжує експлуатацію сільськогосподарської техніки з моменту продажу і до її утилізації. Розглянуті нормативні документи на відповідність вимогам переліку конструкторської документації при її розробці. Вказано на їх невідповідність законодавчим положенням України про стандарти, технічні регламенти та процедури оцінки відповідності. Сформульовані рекомендації із удосконалення конструкторської документації та їх реалізації з метою забезпечення якості технічного сервісу. Purpose of the work. To rework the existing design documentation for developing agricultural machinery taking into account the legislative requirements of the Ukraine. Brief description of the executed work. The analysis of legislative and normative requirements for the design documentation with respect to the guarantee of quality of the technical service of agricultural machinery is executed. The problem of its improvement is substantiated. Requirements for the development of design documentation are formulated. Recommendations regarding the guarantee of its realization are developed. Conclusions. Is determined the problem of the improvement of design documentation according to the execution of the technical service of agricultural machinery. The ways of realization are represented.
To the substantiation of normative documentation with respect to the guarantee of quality of the technical service of agricultural machinery
Keywords: технічний сервіс; сільськогосподарська техніка; нормативні документи; конструкторська документація; технічний регламент; технологічний регламент; technical service; agricultural machinery; normative documents; design documentation; technical regulations; technological regulations